Effects of Outer Shell Layer on the Electronic Transport Behaviors of Sn@SnOx Nanoparticles. Issue 4 (30th November 2020) - Ding, Ang; Li, Tianjun; Wang, Dongxing; Muhammad, Javid; Shah, Asif; Dong, Xinglong; Zhang, Zhidong
Abstract : Tin oxide‐encapsulated tin nanoparticles (Sn@SnO x NCs) are in situ prepared by a modified DC arc‐discharge plasma process. The as‐prepared Sn@SnO x NCs are typically 50–70 nm in diameter with 6 nm of the SnO x shell. The diameter of Sn@SnO x NCs is 50–80 nm and the thickness of the SnO x shell increases to ≈25 nm after heat treatment in a vacuum tube furnace. The effect of SnO x shell thickness on the electrical properties of Sn@SnO x NCs is measured by the four‐probe technique. The results show that the resistivity is described using Bloch–Grüneisen's equation with SnO x shell thickness‐dependent resistivity and SnO x shell thickness‐dependent Debye temperature above the superconducting transition temperature T c . Superconductivity occurs in both Sn@SnO x NCs with different shell thicknesses when the temperature is lower than T c . The T c of the two NCs (3.98 K, 4.15 K) is slightly higher than that of the metal block (3.73 K) due to the electron‐scattering effect of the particles' surface shell. The resistances of the two samples below T c show an exponential decay mode, which is the result of the thermally activated phase slip (TAPS) and quantum phase slip (QPS). Abstract : The electrons in tin oxide‐encapsulated tin nanoparticles (Sn@SnO x NCs) with two different shell thicknesses are conducted in the Bloch–Grüneisen mode above the superconducting transition temperature T c . The electrons of the two Sn@SnOx NCs undergo tunneling below T c (3.98 K, 4.15 K), which is the result of thermally activated phase slip (TAPS) and quantum phase slip (QPS) superimposed.